GAS-PHASE FLAME SYNTHESIS AND PROPERTIES OF MAGNETIC IRON OXIDE NANOPARTICLES WITH REDUCED OXIDATION STATE - Kumfer, Benjamin M (2010)
Iron oxide nanoparticles of reduced oxidation state, mainly in the form of magnetite, have been synthesized utilizing a new continuous, gas-phase, nonpremixed flame method using hydrocarbon fuels. This method takes advantage of the characteristics of the inverse flame, which is produced by injection of oxidizer into a surrounding flow of fuel. Unlike traditional flame methods, this configuration allows for the iron particle formation to be maintained in a more reducing environment. The effects of flame temperature, oxygen-enrichment and fuel dilution (i.e. the stoichiometric mixture fraction), and fuel composition on particle size, Fe oxidation state, and magnetic properties are evaluated and discussed. The crystallite size, Fe(II) fraction, and saturation magnetization were all found to increase with flame temperature. Flames of methane and ethylene were used, and the use of ethylene resulted in particles containing metallic Fe(0), in addition to magnetite, while no Fe(0) was present in samples synthesized using methane.